DAMPAK PENGOPERASIAN ALAT PENANGKAP IKAN TERHADAP SUMBERDAYA IKAN RAWA DANAU BANGKAU - Mijani Rahman (Fish Scientiae, 2019)
Base on qualities category, a fish production from Danau Bangkau swamp waters in some years later was reducing, especially in commercialize fish, and one of causing this problem was a high fishing intensity. The evaluasion of fishing gears impact to fish population have been required to made a concept of sustainable fishing strategy. The measurement of standard length and gonad maturity of fish specimens showed all kind of fishing gears that operated in Danau Bangkau swamp waters included a selectiveness fishing geard category (excepted horizontal gill net) and could be broken to repopulation. A regulation of fishing ground, fishing season and fishing zone have a best solution in order to optimize of fishing activity.